Modifying Saccharomyces cerevisiae Adhesion Properties Regulates Yeast Ecosystem Dynamics - Debra Rossouw (American Society for Microbiology, 2018)
ABSTRACT Physical contact between yeast species, in addition to better-understood and reported metabolic interactions, has recently been proposed to significantly impact the relative fitness of these species in cocultures. Such data have been generated by using membrane bioreactors, which physically separate two yeast species. However, doubts persist about the degree that the various membrane systems allow for continuous and complete metabolic contact, including the exchange of proteins. Here, we provide independent evidence for the importance of physical contact by using a genetic system to modify the degree of physical contact and, therefore, the degree of asexual intraspecies and interspecies adhesion in yeast. Such adhesion is controlled by a family of structurally related cell wall proteins encoded by the FLO gene family. As previously shown, the expression of specific members of the FLO gene family in Saccharomyces cerevisiae dramatically changes the coadhesion patterns between this yeast and other yeast species. Here, we use this differential aggregation mediated by FLO genes as a model to assess the impact of physical contact between different yeast species on the relative fitness of these species in simplified ecosystems. The identity of the FLO gene has a marked effect on the persistence of specific non-Saccharomyces yeasts over the course of extended growth periods in batch cultures. Remarkably, FLO1 and FLO5 expression often result in opposite outcomes. The data provide clear evidence for the role of physical contact in multispecies yeast ecosystems and suggest that FLO gene expression may be a major factor in such interactions. IMPORTANCE The impact of direct (physical) versus indirect (metabolic) interactions between different yeast species has attracted significant research interest in recent years. This is due to the growing interest in the use of multispecies consortia in bioprocesses of industrial relevance and the relevance of interspecies interactions in establishing stable synthetic ecosystems. Compartment bioreactors have traditionally been used in this regard but suffer from numerous limitations. Here, we provide independent evidence for the importance of physical contact by using a genetic system, based on the FLO gene family, to modify the degree of physical contact and, therefore, the degree of asexual intraspecies and interspecies adhesion in yeast. Our results show that interspecies contact significantly impacts population dynamics and the survival of individual species. Remarkably, different members of the FLO gene family often lead to very different population outcomes, further suggesting that FLO gene expression may be a major factor in such interactions.